Clinical and genetic heterogeneity in early onset cerebellar ataxia with retained tendon reflexes. Issue 8 (August 1990) - Filla, A; De Michele, G; Cavalcanti, F; Perretti, A; Santoro, L; Barbieri, F; D'Arienzo, G; Campanella, G
Abstract : A clinical and genetic study was performed on 20 patients affected by early onset cerebellar ataxia with retained tendon reflexes (EOCA). Mean age at onset was 8.8 (SD 6.0) years. The frequency distribution of age of onset significantly differed from the normal distribution. Consanguinity rate was 16.7% and segregation ratio 0.164. As well as ataxia, which was a constant feature, there were signs of involvement of the cortico-spinal tracts and/or peripheral nerves in most patients. Results of neurophysiological studies were not homogeneous, nor were morphological findings of the sural nerve biopsy. The data suggest that EOCA may be genetically and clinically heterogeneous.